Rates and risk of hospitalisation among patients with type 2 diabetes: retrospective cohort study using the UK General Practice Research Database linked to English Hospital Episode Statistics. Issue 1 (23rd September 2013) - Khalid, J. M.; Raluy‐Callado, M.; Curtis, B. H.; Boye, K. S.; Maguire, A.; Reaney, M.
Summary Aims To investigate the rates and risk of hospitalisations in patients with type 2 diabetes (T2D) mellitus in England. Methods This retrospective population‐based cohort study used computerised records from the General Practice Research Database linked to Hospital Episode Statistics data in England. Patients with T2D from January 2006 to December 2010 were selected. Primary outcome measures were all‐cause, non‐diabetes‐related, diabetes‐related and hypoglycaemia‐related hospitalisations. Factors associated with all‐cause and diabetes‐related hospitalisations were investigated with Cox's proportional hazards models. Results Amongst 97, 689 patients with T2D, approximately 60% had at least one hospitalisation during the 4‐year study period. Rates of hospitalisation were as follows: all‐cause, 33.9 per 100 patient‐years (pt‐yrs); non‐diabetes‐related, 29.1 per 100 pt‐yrs; diabetes‐related, 18.8 per 100 pt‐yrs and hypoglycaemia, 0.3 per 100 pt‐yrs. The risk of all‐cause hospitalisation increased with hospitalisation in the previous year, insulin use and the presence of major comorbidities. The risk of a diabetes‐related hospitalisation increased with age, female gender, insulin use, chronic renal insufficiency, hypoglycaemia (as diagnosed by a general practitioner) and diabetes‐related hospitalisation in the previous year. Conclusions Patients with T2D are hospitalised at a considerably high rate for causes directly related with diabetes complications and stay longer in hospital. History of hospitalisation and complications of diabetes were found to be predictive of inpatient hospitalisations suggesting previous hospitalisation episodes could serve as points of intervention. This study highlights important areas for healthcare intervention and provides a reminder for vigilance when risk factors for hospitalisation in patients with T2D are present.